Business Plan for the Council of International Service - Mbacke, Maimouna (2019)
200 million students are enrolled in universities around the world; amongst them, 5.3 million are studying outside their home countries, therefore called international students. The United States is the first destination of international students and India and China are the main sending countries. Due to its demographic boom, sub-Saharan Africa (SSA) boasts the world’s fastest growth rate of tertiary student population. They will reach 22 million in 2027, representing 7% of the world’s higher education students. Nigeria is the first sending country of the region and in total, more than 400,000 students from sub-Saharan Africa are studying outside of their countries. The students choose to travel for multiple reasons: lack of quality or space in local universities, research of new cultural experience and political instability. The process of identifying and enrolling in a university can be very complex for an international student and education agencies act as intermediaries between universities and students to simplify this process. In Senegal, Côte d'Ivoire, Mali and Burkina Faso (SCMB), it is estimated that every year, 7% of tertiary students leave the four countries to study abroad (around 20,000 in the last estimate) making the region a fertile ground for an education placement business to flourish. In comparison, the student outbound ratio in the rest of the continent is at 4.5% and 2% at the global level. Several actors are operating in this market, but they are, for the most part, small and dispersed with an indistinctive offer. In addition, the customers report a poor quality of service and a lack of business ethics. This leaves market gaps both in customer targets and service delivery where a new player can position and succeed. The Council of International Services (CIS) is a student placement agency founded in Senegal in 2020. It aims to support francophone young Africans to get access to high-quality education and professional development opportunities across the world.